A Comparative In Vitro Study of the Effects of Irsha and Chlorhexidine Mouthwashes and Acyclovir on HSV-1 - Ebrahimi, Hooman; Pourshahidi, Sara; Sahraeian, Niloofar; Motamedifar, Mohammad (Journal of Dental School, 2019)
Objective: Being able to cause disease in human, herpes simplex viruses (HSVs) clinically demonstrate themselves as intra-oral, extra-oral or recurrent lesions. The existing acyclovir has the selective anti-herpetic drug to control HSV infections. Due to emerged resistance to this drug and limitations of using it in especial situations, there is a need for alternative treatments such as available mouthwashes. This study aimed to compare two mouthwashes (Irsha and Chlorhexidine) with Acyclovir on HSV-1 in vitro. Methods: In this experimental research, we used MTT (Thiazolyl Blue Tetrazolium Bromide) colorimetric test to determine the cytotoxicity level of three solutions consecutively, antiseptic and nonalcoholic Irsha mouth wash (blue-colored), chlorhexidine 0.2% mouthwash, and acyclovir and absorbed wavelengths were recorded by Eliza Reader. After infecting the cells with different dilutions of HSV-1 in different concentrations of Irsha and chlorhexidine mouthwashes, we analyzed their antiherpetic effects on Vero cells. By using suitable statistical tests in version 15 of SPSS the results were then analyzed. Results: The results showed that in the concentrations of 0.38% for Irsha and 0.003% for chlorhexidine these mouthwashes kill 50% of Vero cells (CC50). After determining CC50, we detected the antiviral effects of Irsha and chlorhexidine mouthwashes and acyclovir solutions. We observed a significant difference between 0.5% concentration of Irsha mouthwash and other concentrations of it. The least logarithm of virus titration was observed in 0.002% concentration of / chlorhexidine mouthwash. Both tested acyclovir concentrations (1250 µgr Mililiter and 2500 µg/mL Mililiter µgr / ) had a similar effect on decreasing virus titre Conclusion: According to our results, anti-herpetic effect of Irsha is less than chlorhexidine and anti-herpetic effect of Acyclovir and Chlorhexidine is stronger than Irsha.